ENHANCE THE HEAT AND FLAME CHARACTERISTICS OF SAGO BRIQUETTES WITH AND WITHOUT ADJUSTERS - Suyatno Suyatno; Helen Riupassa (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2023)
Experimental investigations were conducted to assess the impact of an adjuster on the heating efficiency and flame stability of sago waste briquettes. The adjuster was introduced to maintain a consistent burning distance, thereby enhancing the combustion heat of the fuel. Infrared thermometry was employed to monitor the temperature evolution within the briquette and the combustion load, represented by water in a pan. The findings demonstrate that adding an effective adjuster significantly improves the performance of both the briquettes and the stove, resulting in enhanced effectiveness and efficiency. This is evident from the observed increase in combustion temperature and faster boiling time of the water. The consistent burning distance ensures a stable and uniform heat supply to the briquettes, facilitating more efficient fuel utilization as all parts of the fuel can undergo complete combustion and transfer heat to the pan. Molecular analysis reveals that the stability of the burning distance weakens the Van der Waals bonds within the carbon chain, thereby increasing the reactivity of the fuel molecules. Consequently, the fuel exhibits improved heat absorption capability and becomes highly combustible.